Ecological security assessment of rice production systems in arid regions: a multi-criteria assessment of Iranshahr and Saravan, Iran - Mohammad Reza Shirdeli; Mohammad Reza Asgharipour; Mahmoud Ramroudi; Seyed Ahmad Ghanbari; Alireza Sirousmehr (Scientific Reports)
Abstract This research examines the ecological stability of rice cultivation systems in the arid regions of Iranshahr and Saravan, employing a comprehensive approach that integrates multiple sustainability criteria. The study has integrated the emergy footprint with innovative ecological metrics to quantify the stability and resilience of systems. This study utilized an emergy footprint analysis, integrating ecological footprint and emergy concepts, to assess sustainability. Data were collected through field measurements of agricultural inputs, water use, and soil properties, supplemented by secondary sources such as regional agricultural and meteorological records. The results indicated ecological surpluses in both regions (Iranshahr: 2.92E+09 ha, Saravan: 3.27E+08 ha), along with low Ecological Pressure Index values (0.00184 and 0.00526, respectively), signifying minimal environmental stress. Saravan displayed greater ecological resilience (ERI: 318.97) than Iranshahr (ERI: 86.45); however, both locations showed effective water resource management (WRSI: 176.47 and 147.06, respectively). Soil quality is problematic, as indicated by Soil Quality Degradation Index values of 0.842 (Iranshahr) and 0.886 (Saravan), suggesting moderate degradation. The Socio-Ecological Coupling Index indicated a greater coupling of ecological and societal systems in Iranshahr (147.67) than in Saravan (66.86). The Agricultural System Stability Index values demonstrated highly stable agricultural systems in both study regions (Saravan: 1.51, Iranshahr: 1.37). Even with current global rice cultivation practices, the study shows that careful soil, water, economic, and ecological management can succeed. The study provides a comprehensive method for assessing agricultural system sustainability and valuable insights for arid region agriculture.